1978
DOI: 10.2134/agronj1978.00021962007000050038x
|View full text |Cite
|
Sign up to set email alerts
|

Frost Heaving in Alfalfa Establishment on Soils with different Drainage Characteristics1

Abstract: The susceptibility of alfalfa (Medicago sativa L.) to frost heaving is a major problem in stand establishment in southern Illinois. This study was conducted at Carbondale, Illinois, to determine the effects of frost heaving on the establishment and production of alfalfa cultivars in relation to soil drainage characteristics. Four alfalfa cultivars (‘Cody’, ‘Spredor’, ‘Weevlchek’, and ‘WL‐307’) were seeded on three soil series, a deep well‐drained AIford (Typic Hapluadalf, fine‐silty mixed mesic), a moderately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Damage was particularly severe on much soils and sandy loams, while it was less marked on clay loam. Russell et al (1978) observed that soil moisture had a major influence on number and extent of alfalfa seedlings heaved. Plants heaved most when the perched water table was at or near the soil surface.…”
Section: Loss Of Growthmentioning
confidence: 98%
See 2 more Smart Citations
“…Damage was particularly severe on much soils and sandy loams, while it was less marked on clay loam. Russell et al (1978) observed that soil moisture had a major influence on number and extent of alfalfa seedlings heaved. Plants heaved most when the perched water table was at or near the soil surface.…”
Section: Loss Of Growthmentioning
confidence: 98%
“…x Biswell et al 1953MacGillivray and Hartley 1973Soderstriim 1973 x Low 1969, 1975Shaw et al 1987Zalasky 1980I Graber 197 1 Sutton 1968, 1991, 1992Haasis 1923Shimada et al 1982cox 1979Gill 1977Kinbacher 1956Cox and Mason 1955Biswell et al 1953Lamb 1936 Factors Factors affecting forest heaving of forest tree species and agricultural crops Haasis 1923Brink et al 1967Russell et al 1978Sutton 1969, 1992Cooper 1940Perfect et al 1987Shimada et al 1982;Portz 1967Gill 1977 Hook. and Am.)…”
Section: Loss Of Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical damage to the roots can also be caused by soil heaving, primarily in imperfectly drained soils exposed to frequent freeze-thaw cycles (Holmes and Robertson 1960;Russell et al 1978). Significant losses of alfalfa stands due to frost heaving frequently occur in the Atlantic provinces of Canada (Grant and Saini 1973) and in the southern areas of Québec (Pesant et al 1978).…”
Section: Soil Moisture and Icementioning
confidence: 99%
“…nonequilibrium manner (Olien 1964) (Lamb 1967) and legume forages (Russell et al 1978 (Tesar and Yager 1985). Other workers (Schaeffer et al 1986) …”
Section: Elimination Of Heterosis In Cornmentioning
confidence: 99%